Catalytic enantioselective synthesis of P-stereogenic compounds. - Harvey, J; Gouverneur, V (2010)
Catalytic enantioselective strategies have become synthetically useful to access P-stereogenic phosphines. To date, enantioselective desymmetrisations and dynamic kinetic resolutions dominate the field. Desymmetrisation strategies do not necessarily require the formation of a P-carbon or P-heteroatom bond. This approach has been validated with variable levels of success using organocatalysed asymmetric deprotonation (chiral diamine) or methylation (phase transfer catalysis), enzyme-mediated esterification, rhodium catalysed [2+2+2] cycloadditions and more recently molybdenum-based ring closing metathesis. The dynamic kinetic resolution of racemic P-templates relying on a P-C bond-forming event has been the object of extensive investigations, which have culminated with the arylation and alkylation (benzylation) of equilibrating diastereomeric palladium, platinum or ruthenium phosphido complexes. Although all these routes allow access to a myriad of highly interesting P-stereogenic compounds, the level of enantiocontrol is substrate- and reactant-dependent. Pleasingly, ee's up to 98% were obtained on selected systems.